(untitled) (UNED Research Journal, 2016)
The view that college students have about prostitution is poorly known, and the little research that is available has been done in the USA and Spain. To study the perceptions and knowledge of college students about prostitution in Costa Rica, we interviewed sex workers, directors of foundations and 200 students from San José and Puntarenas, Costa Rica. Most students have a fairly realistic view of the phenomenon; most believe that people enter sex work through a combination of need and choice, that sex abuse is not inherent, that most sex workers have families to take care of with limited education. In regards to the clients most students believe the majority are varied in age, tend to have families and often become regulars. Our results are similar to those reported for Spain.